ANALISIS SISTEM AKUNTASI PENERIMAAN KAS PADA KOPERASI PURNA KARYA PERTAMINA (PURNAMA) CABANG MEDAN - Rayhan Ananda; Debora Tambunan; Arsyaf Tampubolon (Jurnal Mahkota Bisnis (Makbis), 2025)
This research aims to determine the application of the cash receipts accounting system for the sale of 3Kg LPG gas at the Medan branch of the Pertamina retired workers' cooperative. The data collection methods used in this research were observation, documentation, interviews. Cash is the most liquid asset that a company can have because cash is a type of current asset for every company transaction both inside and outside the company can affect cash. This research was carried out by obtaining qualitative data. The qualitative data in this research was obtained by conducting direct research with the leadership of the Pertamina Purna Karya Cooperative, Medan Branch. Pertamina Purna Karya Cooperative has several types of cash receipts, namely Cash Receipts from LPG Gas Sales and Cash Receipts from Transport Fees. The results of this research show that the cash receipts accounting system at the Pertamina retirement cooperative for the sale of LPG gas can provide accurate related data. The obstacle that occurs is that when the base wants to make payments, errors or disruptions often occur through the Mandiri Value Chain system. The Pertamina retired workers cooperative must improve services to consumers by providing assistance in a direct payment system for LPG gas sales so that problems do not occur and consumer complaints can be resolved.